2021
DOI: 10.3390/molecules26133996
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antidiabetic Activity of the Shikonin by Allosteric Inhibition of Protein-Tyrosine Phosphatase 1B (PTP1B) Using State of Art: An In Silico and In Vitro Tactics

Abstract: Diabetes mellitus is a multifactorial disease that affects both developing and developed countries and is a major public health concern. Many synthetic drugs are available in the market, which counteracts the associated pathologies. However, due to the propensity of side effects, there is an unmet need for the investigation of safe and effective drugs. This research aims to find a novel phytoconstituent having diminished action on blood glucose levels with the least side effects. Shikonin is a naturally occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 28 publications
4
27
0
Order By: Relevance
“…MD simulations also suggest that shikonin could be a lead molecule for inhibiting PTP1B. The powerful inhibition of PTP1B by shikonin was determined experimentally (IC50 = 8.72 M), confirming the antidiabetic effects of the shikonin scaffold [ 160 ].…”
Section: Molecular Docking and Molecular Dynamics Predicted Anti-diabetic Activitymentioning
confidence: 86%
See 2 more Smart Citations
“…MD simulations also suggest that shikonin could be a lead molecule for inhibiting PTP1B. The powerful inhibition of PTP1B by shikonin was determined experimentally (IC50 = 8.72 M), confirming the antidiabetic effects of the shikonin scaffold [ 160 ].…”
Section: Molecular Docking and Molecular Dynamics Predicted Anti-diabetic Activitymentioning
confidence: 86%
“…The ability of shikonin, a natural naphthoquinone dying pigment, to inhibit PTP1B was evaluated through a complex approach involving in silico and in vitro methods [ 160 ]. Shikonin was docked at its putative binding site from 1AAX structure [ 161 ], which allowed the identification of crucial residues involved in the interaction.…”
Section: Molecular Docking and Molecular Dynamics Predicted Anti-diabetic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in vivo S-treatment resulted in decreased weight gain and hepatic fat accumulation, enhanced glucose tolerance, augmented fatty acid oxidation-associated genes and ameliorated hepatic insulin signaling in mice ( Bettaieb et al, 2015 ; Gwon et al, 2015 ). The anti-diabetic potential of S has been further demonstrated in recent studies, which showed that S could act as a free fatty acid receptor 4 (FFA4) agonist in HT-29 cells and lower plasma glucose levels in diabetic mice ( Xu et al, 2021 ), whereas it suppressed protein tyrosine phosphate 1B (PTP1B), during in silico and in vitro experiments ( Saeed et al, 2021 ). At this point, it should be noted that, to the best of our knowledge, there has not been a related study on the effect of either the A enantiomer or the chirality of A/S on DM/obesity/glucose uptake.…”
Section: Introductionmentioning
confidence: 98%
“…Diabetes is a well-known chronic disease that affects the ability of the human body to convert glucose into energy [1] [2]. In addition to causing blindness and kidney failure, diabetes is a leading cause of heart attacks, strokes, and lower-limb amputations, among other deadly diseases [3].…”
Section: Introductionmentioning
confidence: 99%